EFFECT OF AGING TREATMENT ON THE MICROSTRUCTURES AND HARDNESS OF Fe-Ni-Cr SUPERALLOY - Ridhwan, J.; Zulfattah, Z.; Selamat, Mohd Zulkefli; Hafidzal, M.H.M (UMP Publisher, 2013)
Aging treatment was conducted on Fe-Ni-Cr superalloy to observe its effect on the microstructures and hardness of the material. Solution treatments were carried out at 900oC, 975oC, 1050oC, and 1125oC followed by water quenching. The samples were further treated with a double aging treatment at 720oC and 650oC for 4 hours and 12 hours respectively. Materials characterization techniques such as SEM, XRD, and optical microscopy were used to analyze the heat-treated samples. The Fe-Ni-Cr superalloy formed mainly a dendritic austenitic structure with Cr23C6 precipitated along the grain boundaries. Increase in solution treatment temperature results in dissolution of chromium carbide, coarser grain, and lower hardness for non-aged samples. Double aging treatment produced more chromium carbide, higher hardness, but no apparent change in grain size. Neither quenching nor aging treatments caused any phase transformation. The highest hardness value of 220.4 Hv was recorded for the sample solution treated at 1125oC for 2 hours and water quenched, followed by 2-step aging at temperature 720oC and 650oC for 4 hours and 12 hours respectively, and air cooled.